Revisiting two hypotheses on the “domestication syndrome” in light of genomic data - A. S. Wilkins (Вавиловский журнал генетики и селекции)
Domesticated mammals of many different species share a set of physical and physiological traits that are not displayed by any of their wild progenitors. This suite of traits, now termed the “domestication syndrome” (DS), has been a puzzle since Charles Darwin discovered it. Two general explanations of its basis have been proposed, which in principle, could also apply to other vertebrates, such as fish and birds, whose domesticated varieties show some of its elements. The two ideas are termed here, respectively, the thyroid hormone hypothesis or the THH, and the neural crest cell hypothesis, the NCCH. The two ideas make distinctly different genetic predictions. Here, the current relevant evidence from genomics is evaluated and it is concluded that the NCCH has more support. Nevertheless, one set of observations, from chickens, suggest a potentially important role of altered thyroid metabolism in domestication. In addition, recent studies indicate the possibility of additional genetic factors in domestication, affecting tameness and sociality, that may go beyond either hypothesis. The tasks that lie ahead to fully ascertain the genetic bases of the “domestication syndrome” and the behaviors that characterize mammalian domestication are discussed briefly.